TINGKAT KEPUASAN MAHASISWA TERHADAP KARAKTERISTIK DOSEN DI STKIP MUHAMMADIYAH SAMPIT - Sudarmono Sudarmono; Apuanor Apuanor; Sulis Setiyowati (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2019)
This study aimed to determine the Student Satisfaction Differences on Lecturer Characteristics of the big five factors of Extraversion, Agreeableness, Conscientiousness, Neuroticism and Openness to experience in Teaching and Learning at the Educational Program of Economic Studies of STKIP Muhammadiyah Sampit. This research was a comparative research using quantitative approach. The subjects of the study were the 4th semester students of the Educational Program of Economic Studies of STKIP Muhammadiyah Sampit which amounted to 28 person. The data analysis used was Analysis of One Path Variant (One Way Anova) Based on the results of data analysis, it could be concluded that there were the student satisfaction differences on the characteristics of lecturers type Extraversion, Conscientiousness, Neuroticism and Openness to experience. This was indicated by the value F arithmetic> Ftable; 3.364> 2.26 with significant value p = 0.020